Perspectives in Computational Complexity 2014
DOI: 10.1007/978-3-319-05446-9_7
|View full text |Cite
|
Sign up to set email alerts
|

Progress on Polynomial Identity Testing-II

Abstract: We survey the area of algebraic complexity theory; with the focus being on the problem of polynomial identity testing (PIT). We discuss the key ideas that have gone into the results of the last few years. Subject Classification (2010). Primary 68Q25, 68W30; Secondary 12Y05, 13P25. Mathematics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
57
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 51 publications
(42 reference statements)
0
57
0
Order By: Relevance
“…One of the main reasons for interest in this problem is the connection between PIT algorithms and circuit lower bounds (Heintz & Schnorr [HS80], Kabanets & Impagliazzo [KI03] and Agrawal [Agr05,Agr06]). Refer to surveys for a detailed treatment of PIT [Sax09,AS09].…”
Section: Introductionmentioning
confidence: 99%
“…One of the main reasons for interest in this problem is the connection between PIT algorithms and circuit lower bounds (Heintz & Schnorr [HS80], Kabanets & Impagliazzo [KI03] and Agrawal [Agr05,Agr06]). Refer to surveys for a detailed treatment of PIT [Sax09,AS09].…”
Section: Introductionmentioning
confidence: 99%
“…It is also known that any sub-exponential time algorithm for PIT implies a lower bound [KI03,Agr05]. See also the surveys [Sax09,Sax14,SY10].…”
Section: Introductionmentioning
confidence: 99%
“…In 2004, Impagliazzo and Kabanets [KI04] showed that a deterministic polynomial time algorithm for PIT implies lower bounds (either NEXP ⊂ P/poly or permanent does not have polynomial size arithmetic circuits), thus making it one of the central problems in algebraic complexity. Following [KI04], intense efforts over the last decade have been directed towards de-randomizing PIT (see for instance [SY10,Sax14]). The attempts fall into two categories: considering special cases ( [Sax14]), and optimizing the random bits used in the Schwartz-Zippel test [BHS08,BE11].…”
Section: Introductionmentioning
confidence: 99%
“…Following [KI04], intense efforts over the last decade have been directed towards de-randomizing PIT (see for instance [SY10,Sax14]). The attempts fall into two categories: considering special cases ( [Sax14]), and optimizing the random bits used in the Schwartz-Zippel test [BHS08,BE11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation